2022
DOI: 10.1007/s00210-022-02351-y
|View full text |Cite|
|
Sign up to set email alerts
|

Ameliorative effects of quercetin against hepatic toxicity of oral sub-chronic co-exposure to aluminum oxide nanoparticles and lead-acetate in male rats

Abstract: The present study was designed to evaluate the probable ameliorative role of quercetin (QCN) against oxidative hepatotoxicity induced by aluminum oxide nanoparticles (Al2O3NPs) with a diameter < 30 nm and lead acetate (Pb) co-exposure in adult male Sprague–Dawley rats. Rats were weighed and allocated to seven groups (n = 10 each) and were treated orally via orogastric gavage for 60 successive days: rats of the 1st group were kept as control given distilled water (1 ml/kg), rats of the 2nd group received 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…The change in body weight is one of the most widely used parameters in toxicological assessments to indicate the toxic effects of a substance on the health status of animals (Wang et al 2019a ). Thus, in most medical and environmental toxicology research on the effects of certain substances on the body, animal body mass and organ mass have been frequently measured (Abo-El-Sooud et al 2023 ; Fadil et al 2023 ). In the current study, ZNPs-exposed rats showed a significant reduction in daily weight gain compared to their respective control.…”
Section: Discussionmentioning
confidence: 99%
“…The change in body weight is one of the most widely used parameters in toxicological assessments to indicate the toxic effects of a substance on the health status of animals (Wang et al 2019a ). Thus, in most medical and environmental toxicology research on the effects of certain substances on the body, animal body mass and organ mass have been frequently measured (Abo-El-Sooud et al 2023 ; Fadil et al 2023 ). In the current study, ZNPs-exposed rats showed a significant reduction in daily weight gain compared to their respective control.…”
Section: Discussionmentioning
confidence: 99%
“…To hinder the toxicological effects, in particular the oxidative stress engendered by Al 2 O 3 NPs, many endeavors have been dedicated to discovering natural products with intrinsic antioxidant capacities. The major studies focused on antioxidant-derived plants that contain bioactive polyphenolic compounds such as quercetin to reduce oxidative damage in hepatic cells after treatment with Al 2 O 3 NPs [ 17 , 18 , 19 ]. So far, very little attention has been paid to antioxidant-derived insects to tackle the deleterious consequences of the metal NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Quando ativadas, pela presença de Pb, por exemplo, células de defesa como macrófagos secretam NO e aumentam os níveis desse radical tóxico para o tecido(Abdel Moneim, 2016). Em conformidade com nosso estudo, ratos expostos oralmente a 50 mg/kg de acetato de Pb durante 60 dias também apresentaram dilatação de capilares sinusóides e maior incidência de infiltrados leucocitários no fígado (Abo-EL- Sooud et al, 2022). Codornas expostas oralmente a 50, 250, 500 e 1000 mg/kg de acetato de Pb durante 49 dias apresentaram diminuição na atividade enzimática da SOD, CAT e GST, e…”
unclassified